2021
DOI: 10.3390/insects12040289
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Olfactory Sensilla across the Antennae and Maxillary Palps of Bactrocera dorsalis (Diptera: Tephritidae)

Abstract: The sensilla on the antennae and maxillary palps are the most important olfactory organs, via which the insect can perceive the semiochemicals to adjust their host seeking and oviposition behaviors. The oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), is a major agricultural quarantine pest infesting more than 250 different fruits and vegetables. However, the sensilla involved in olfaction have not been well documented even though a variety of control practices based on chemical communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…The presence or absence of sensilla may be associated with adaptations to insect lifestyle, as reported for the antennal sensilla of four fig wasps (Hymenoptera: Chalcidoidea) with coeloconic sensilla occurring only in that entering the fruit to lay eggs (Yang et al, 2018). The occurrence of chaetica sensilla only in the antennal scape and pedicel found for A. flavissima is similar to that reported for Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) (Fu et al, 2012) and Bactrocera dorsalis (Diptera: Tephritidae) (Liu et al, 2021). The absence of cuticular pores and the flexible socket at the base of that sensillum indicates that it is a mechanoreceptor such as reported for other insects (Keil & Steinbrecht, 1984).…”
Section: Discussionsupporting
confidence: 84%
“…The presence or absence of sensilla may be associated with adaptations to insect lifestyle, as reported for the antennal sensilla of four fig wasps (Hymenoptera: Chalcidoidea) with coeloconic sensilla occurring only in that entering the fruit to lay eggs (Yang et al, 2018). The occurrence of chaetica sensilla only in the antennal scape and pedicel found for A. flavissima is similar to that reported for Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) (Fu et al, 2012) and Bactrocera dorsalis (Diptera: Tephritidae) (Liu et al, 2021). The absence of cuticular pores and the flexible socket at the base of that sensillum indicates that it is a mechanoreceptor such as reported for other insects (Keil & Steinbrecht, 1984).…”
Section: Discussionsupporting
confidence: 84%
“…The antennae and the maxillary palps, covered by numerous sensilla, are the primary olfactory organs in fruit flies. The multiporous sensilla trichodea are responsible for detecting volatile plant compounds and pheromones [31]. The toxic baits were more attractive to medflies or slightly repellent to A. obliqua during periods shorter than 360 minutes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This was also evident from the fact that the excised ovipositor could respond to GOL in the EOG experiments. SEM studies done previously on different appendages of tephritids including B. dorsalis (Zhang et al, 2012;Liu et al, 2021) reported differences in the type and density of sensillae on antennae and ovipositor. Significant difference in the density of the sensillae on the ovipositor compared to the antenna did not abolish the ovipositor response to GOL, which was comparable to that of the antenna.…”
Section: Discussionmentioning
confidence: 93%